Sustaining Standard of Living Amidst Volatile Oil Prices – Lessons from the Gulf Countries - Al Sabah, Khaleefah Jabar; Palliam, Ralph; Salem, Athmar Al (Consilience, 2016)
Improving living standards amidst falling oil prices among countries relying heavily of an ample supply of oil presents numerous challenges. Therefore the relationship associated with oil price changes with identifiable metrics that explain standards of living becomes critical. The management of wealth; sustaining a standard of living; peculiarities of oil trade; oil price determination; and management and the uncharacteristic application of supply and demand are presented. Since aspects of the world oil market remain unclear and opaque, society is in need of credible research and verifiable theory. Data relating to Kuwait over a 32-year period (1983 – 2014) were obtained. Five independent variables: investment growth; inflation; percentage change in price per barrel; unemployment; and percent change in the number of incarcerations are regressed with a change in real GDP (dependent variable). Finally, to determine the robustness of the model, the Durbin-Watson test was used. The coefficient of determination (r2) suggests that 66.24% of variations in lifestyle can be explained by variations in the five independent variables (p<0.01). Standards of living can be sustained by increasing growth in investment, decreasing inflation, decreasing unemployment and incarcerations and most important increase in price of oil. This study places Kuwait as a proxy for the Gulf Countries and should ideally be extended to the other five Gulf Countries. Comparative studies over multiple periods of time ought to be undertaken to measure the robustness of differing sustainability measures.